Microsatellite Instability in Urine: Breakthrough Method for Bladder Cancer Identification - Manuel Alejandro Rico-Méndez; María de la Luz Ayala-Madrigal; Anahí González-Mercado; Melva Gutiérrez-Angulo; Jorge Adrián Ramírez de Arellano Sánchez; Saul Armando Beltrán-Ontiveros; Betsabe Contreras-Haro; Itzae Adonai Gutiérrez-Hurtado; José Miguel Moreno-Ortiz (Biomedicines, 2024)
Bladder cancer (BC) is the most common neoplasm of the urinary system and ranks tenth in global cancer incidence. Due to its high recurrence rate and the need for continuous monitoring, it is the cancer with the highest cost per patient. Cystoscopy is the traditional method for its detection and surveillance; however, this is an invasive technique, while non-invasive methods, such as cytology, have a limited sensitivity. For this reason, new non-invasive strategies have emerged, analyzing useful markers for BC detection from urine samples. The identification of tumor markers is essential for early cancer detection and treatment. Urine analysis offers a non-invasive method to identify these markers. Microsatellite instability (MSI) has been proposed as a promising marker for tumor cell detection and guided targeted therapies. Therefore, this review aims to explore the evidence supporting the identification of MSI in exfoliated bladder tumor cells (EBTCs) in the urine, emphasizing its potential as a non-invasive and clinically effective alternative for tumor identification. Furthermore, establishing clinical guidelines is crucial for standardizing its application in oncological screening and validating its clinical utility.